Efisiensi Produksi Usahatani Ubi Kayu dengan Pendekatan Stockhastic Frontier di Provinsi Lampung - Teguh Endaryanto; Wan Abbas Zakaria; Lidya Sari Mas Indah; Abdul Mutolib (Politeknik Negeri Lampung., 2023)
This study aims to analyze the efficiency of production and the factors that affect the technical efficiency of cassava in Lampung Province. This research was conducted in Central Lampung Regency as the center of cassava production in Lampung Province using a survey method. The number of samples was determined using stratified random sampling so that the total sample size was 100 farmers. Data were collected in August 2020. Farm income was analyzed using R / C and the level of production efficiency was analyzed by the stockhastic frontier production function. The results showed that cassava farming was not technically efficient, but was economically and costly efficient. The total cost of cassava farming income is Rp. 13,959,551.45 per ha with RC of 2.35, so that cassava farming is profitable for cultivation. There are three variables that have a significant effect on the technical efficiency of cassava farming, namely farming experience, age and participation in extension.